Perancangan dan Pembuatan Mesin Pengaduk Sampah Organik - Ignatius Aris Hendaryanto; Galuh Bahari; Radhian Krisnaputra (Jurnal Engine: Energi, Manufaktur, dan Material, 2025)
Waste is a byproduct of production activities, both in the industrial and household sectors. Solid waste, commonly known as garbage, can be divided into organic and inorganic waste. Organic waste from households, such as food scraps and plant materials like wood, twigs, or leaves, can be converted into compost or organic fertilizer that has economic value. The process of organic waste treatment requires a mixer machine to blend the chopped waste with other additional materials. In this study, the design and construction of an organic waste mixer machine were carried out. The mixing mechanism uses two ribbon-shaped twisted (helical) blades that rotate in opposite directions. As they spin, they produce a rotating movement while shifting to the left and right, creating a more even mixing effect. The shaft and mixing blades are rotated by the main drive, a 1 hp single-phase electric motor with a speed of 1420 rpm. From the electric motor, the speed is reduced using a speed reducer gearbox with a 40:1 ratio, bringing the shaft and blade rotation speed to 35,5 rpm. The mixing force generated on the mixer blade is 752,6 N.